Unified viscoplasticity modelling and its application to fatigue-creep behaviour of gas turbine rotor - Benaarbia, Adil; Rae, Y.; Sun, Wei (Elsevier, 2018)
This paper presents an elasto-visco-plastic finite element modelling framework including the associated UMAT codes to investigate the high temperature behaviour of gas turbine rotor steels. The model used in the FE study is an improved and unified multi-axial Chaboche-Lemaitre model which takes into account non-linear kinematic and isotropic hardening. The computational methodology is a three-dimensional framework following an implicit formulation and based on a radial return mapping algorithm. The UMAT is calibrated and validated across isothermal hold-time cyclic tests. The methodology developed is applied to a classical industrial gas turbine rotor where the study focuses its attention on the deformation heterogeneities and critical high stress areas within the rotor structure. The effect of thermal transients and geometry singularities on the development of residual stresses is underlined. Finally, the potential improvements and extensions of such FE viscoplastic analysis is discussed.